Drivers of change of Thwaites Glacier, West Antarctica, between 1995 and 2015 - Santos, Thiago Dias Dos; Barnes, Jowan M.; Goldberg, Daniel N.; Gudmundsson, G. Hilmar; Morlighem, Mathieu (Geophysical Research Letters, 2021)
We run several transient numerical simulations applying these three perturbations individually. Our results show that ocean-induced ice-shelf thinning generates most of the observed grounding line retreat, inland speed-up, and mass loss, in agreement with previous work. We improve the agreement with observed inland speed-up and thinning by prescribing changes in ice-shelf geometry and a reduction in basal traction over areas that became ungrounded since 1995, suggesting that shelf breakups and thinning-induced reduction in basal traction play a critical role on Thwaites's dynamics, as pointed out by previous studies. These findings suggest that modeling Thwaites's future requires reliable ocean-induced melt estimates in models that respond accurately to downstream perturbations.